The Implementation of Social Values in Shaping Social Behavior in Students of Grade IV at Primary School - Felista Imunora; Nathalia Yohana Johannes; Leonid Ritiauw (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study is motivated by the escalating challenges of the digital era and globalization, which have adversely impacted elementary students' social behavior, leading to a decline in manners and direct interpersonal interaction. The research aims to describe and analyze the implementation of social values in shaping the social behavior of fourth-grade students at Primary School 7 Ambon. Employing a descriptive qualitative approach, data was gathered through participatory observation, in-depth interviews, and documentation. The subjects, selected via purposive sampling, included the school principal, three fourth-grade teachers, and six students. Data analysis followed an interactive model involving condensation, display, and verification. The findings reveal that social values—specifically gotong royong (cooperation), responsibility, discipline, honesty, tolerance, and courtesy—were successfully integrated through three primary strategies: modeling, habituation, and positive reinforcement. Despite multidimensional challenges such as digital disruption and diverse family backgrounds, the implementation significantly improved students' prosocial behavior, fostering mutual respect and reducing peer conflict. This study contributes a strategic framework for educators to strengthen character education through contextual integration. It underscores that a cohesive synergy between school-based habituation and parental involvement is essential for the sustainable internalization of social values in contemporary education.